Status and Opportunities of Zinc Ion Hybrid Capacitors: Focus on Carbon Materials, Current Collectors, and Separators - Wang, Yanyan; Sun, Shirong; Wu, Xiaoliang; Liang, Hanfeng; Zhang, Wenli (Nano-Micro Letters, 2023)
Zinc ion hybrid capacitors (ZIHCs), which integrate the features of the high power of supercapacitors and the high energy of zinc ion batteries, are promising competitors in future electrochemical energy storage applications. Carbon-based materials are deemed the competitive candidates for cathodes of ZIHC due to their cost-effectiveness, high electronic conductivity, chemical inertness, controllable surface states, and tunable pore architectures. In recent years, great research efforts have been devoted to further improving the energy density and cycling stability of ZIHCs. Reasonable modification and optimization of carbon-based materials offer a remedy for these challenges. In this review, the structural design, and electrochemical properties of carbon-based cathode materials with different dimensions, as well as the selection of compatible, robust current collectors and separators for ZIHCs are discussed. The challenges and prospects of ZIHCs are showcased to guide the innovative development of carbon-based cathode materials and the development of novel ZIHCs. Highlights: 1 History and benefits of zinc ion hybrid capacitors are introduced. 2 Carbon materials with different dimensions are developed for the cathodes. 3 Relationship between carbon structures and capacitive performances are discussed. 4 Current collectors and separators are firstly showcased and summarized.